Can conventional phase-change memory devices be scaled down to single-nanometre dimensions?. (9th December 2016) - Hayat, Hasan; Kohary, Krisztian; Wright, C David
Abstract: The scaling potential of 'mushroom-type' phase-change memory devices is evaluated, down to single-nanometre dimensions, using physically realistic simulations that combine electro-thermal modelling with a Gillespie Cellular Automata phase-transformation approach. We found that cells with heater contact sizes as small as 6 nm could be successfully amorphized and re-crystallized (RESET and SET) using moderate excitation voltages. However, to enable the efficient formation of amorphous domes during RESET in small cells (heater contact diameters of 10 nm or less), it was necessary to improve the thermal confinement of the cell to reduce heat loss via the electrodes. The resistance window between the SET and RESET states decreased as the cell size reduced, but it was still more than an order of magnitude even for the smallest cells. As expected, the RESET current reduced as the cells got smaller; indeed, RESET current scaled with the inverse of the heater contact diameter and ultra-small RESET currents of only 19 μ A were achieved for the smallest cells. Our results show that the conventional mushroom-type phase-change cell architecture is scalable and operable in the sub-10nm region.